PASSWORD PROTECTION TPM LINDUNGI HAK CIPTA KONTEN ONLINE COURSE DARI PENGAMBILALIHAN ILEGAL - Pradika, Agun (JIPRO: Journal of Intellectual Property, 2024)
The use of the Password Protection Online Course as a Technological Protection Measure (TPM) then gives rise to various dynamics of pros and cons regarding the impacts. So in this case it is necessary to conduct a study regarding the dynamics of using Password Protection Online Courses as a Technological Protection Measure (TPM) and Efforts to Protect Copyright of Online Course Content against Illegal Takeover of Access Rights Through Password Protection. The type of research used is normative research with a normative juridical approach. The results of this research show that Technologies Protection Measures (TPM) is a technology that can be used to protect documents from digital works with copyright. Efforts to realize copyright protection are carried out by creators to protect their creations from piracy or text mining which may be carried out on the online course content they create. The use of password protection utilizes the use of security technology to protect copyright and economic rights as regulated in articles 52 and 53 of the Copyright Law. Thus, it can be concluded that collaborative efforts between security technology or TPM and the legal provisions in the Copyright Law, ITE Law, WIPO and Bern Convention on Corporate Rights are quite good and provide comprehensive protection. Regulating the use of security technology includes protecting the moral and economic rights of a work. This provides benefits for creators in protecting their creative works in digital form and their distribution, the regulations for which have been implemented in the Copyright Law.